DIRECTIVES SPEECH ACT IN THE UTTERANCES OF CHARACTERS IN THE MOVIE ENTITLED WISH DRAGON - Valentino Giovani; Yuli Widiana (Humaniora Scientia, 2022)
The research is entitled â€œDirectives Speech Act in The Utterances of Characters in The Movie Entitled Wish Dragonâ€ The research aimed to find out and classify the types of directive speech acts used by the characters in the movie of Wish Dragon and to explain the functions of each type of directive speech act based on the contexts. The method applied was the descriptive qualitative method.Â  The data of this research were in the form of words, phrases, clauses, and sentences that contain directive speech acts. The technique of collecting data was conducted by collecting the data from the Wish Dragon movie, classifying types of directives speech act, and the last, describing the function of each type of directive speech act. Furthermore, the technique of data analysis was based on Kreidler's (1998) classification of directive speech acts. The types are commands, requests, and suggestions. The next step was explaining the functions of each type of directive speech acts based on the pragmatic contexts. There were three types of directives speech acts used by the characters in the movie of Wish Dragon, such as command, request, and suggestion. The command functioned to demand, to direct, to order, and to forbid. The request functioned to ask, to beseech, and to entreat. The suggestion functioned to recommend, to advise, to counsel, to caution, and to warn. The most dominant type of directive speech act used by the characters was the directive speech act command. It could be influenced by the social status between one and another character. Some character who conveyed the command has higher social status or authority.